Pembangunan dan Perubahan Sosial di Minahasa: Sebuah Pengamatan Awal dari Luar - Riwanto Tirtosudarmo; Roosmalawati Roosmalawati (Antropologi Indonesia, 1995)
The article is a preliminary study on the social impact of development in Minahasa. The authors try to identify, development problems as exhaustable as possible. The factors that have influenced the development in Minahasa are originated from the Minahasa community themselves and from government policies. The central government has exercised a strong influence on local condition. Local government which functions on behalf of the central government exhibit such characteristics a bureaucratic, hierarchic, and paternalistic. On the other hand, the Minahasa people are democratic and egalitarian in their social relationship. The difference between both value systems does not come into conflict, because the Minahasans channel their aspirations through the church and are able to make adjustment.